FACT-CHECKING IN THE AGE OF MISINFORMATION: LINGUISTIC STRATEGIES FOR ACCURATE REPORTING - Chelsi Aprilia Ashari; Firna Apriani; Ainun Jariyah; Fadia Rezky Amelia; Safitri Rahmadani Suraj; Helsa Zein (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2024)
Fact-checking journalism has become a common practice to counteract misinformation. In an era of widespread disinformation, the factuality of information is crucial. This research explores linguistic strategies for fact-checking accurate reporting. With a focus on factuality, linguistic approaches are analyzed to identify effective methods in combating misinformation. Specifically, we studied whether there are differences in perceptions based on Linguistic Strategies for Accurate Reporting, dan how often fact-checkers conduct fact-checking. It integrates linguistic understanding with journalism practice to strengthen the reliability of information presented to the public.